2013
DOI: 10.1164/rccm.201212-2154oc
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationship between Cognitive Function and Pneumonia

Abstract: Rationale: Relationships between chronic health conditions and acute infections remain poorly understood. Preclinical studies suggest crosstalk between nervous and immune systems. Objectives: To determine bidirectional relationships between cognition and pneumonia. Methods: We conducted longitudinal analyses of a population-based cohort over 10 years. We determined whether changes in cognition increase risk of pneumonia hospitalization by trajectory analyses and joint modeling. We then determined whether pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
189
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(200 citation statements)
references
References 40 publications
6
189
5
Order By: Relevance
“…The reason for this finding remains unclear. Lung disease and impaired lung function are reportedly associated with inferior cognitive performance [37][38][39][40]. We speculate that impaired lung function brought about by pneumonia in patients with dementia may lead to a further decline in cognitive function, making it less likely that a patient will be able to return home.…”
Section: Discussionmentioning
confidence: 86%
“…The reason for this finding remains unclear. Lung disease and impaired lung function are reportedly associated with inferior cognitive performance [37][38][39][40]. We speculate that impaired lung function brought about by pneumonia in patients with dementia may lead to a further decline in cognitive function, making it less likely that a patient will be able to return home.…”
Section: Discussionmentioning
confidence: 86%
“…Confirmatory studies, designed to examine markers of oxidative stress (34,35), inflammation (e.g., IL-18) (35,(43)(44)(45), and oxygenation postoperatively as potential mediators of the observed relationships between allograft ischemic time, oxygenation, and cognitive function, are required to validate our observations. Related future studies are required to examine whether the previously identified relationship between prolonged allograft ischemic time and long-term survival (34) is mediated by cognitive impairment and the potential adverse events related to such impairment (i.e., functional impairment, medication nonadherence, infectious complications) (46,47). Importantly, given the collinearity between graft ischemic time and cardiopulmonary bypass time and the standard use of cardiopulmonary bypass for bilateral lung transplantation at this center, the use and duration of cardiopulmonary bypass remains a potentially modifiable risk factor for cognitive decline after lung transplantation (32,33).…”
Section: Original Researchmentioning
confidence: 99%
“…Each year, 1.1 million patients are hospitalized with pneumonia, and the vast majority of patients survive to hospital discharge (2). Once believed to be an acute illness with minimal repercussions, pneumonia is increasingly recognized to be a fundamental turning point in patients' lives (3), resulting in new functional limitations (4), cognitive decline (4,5), and increased long-term mortality (3,(6)(7)(8). The causes of this persistent mortality burden remain unclear, and reasons for rehospitalization may identify important sources of morbidity in this population.…”
mentioning
confidence: 99%